FRI0500 Extracranial vascular affection in giant cell arteritis. (12th June 2018) - Martín-Varillas, J.L.; Loricera, J.; Prieto-Peña, D.; Narváez, J.; Aurrecoechea, E.; Villa, I.; Castañeda, S.; Gómez-Arango, C.; Mera, A.; Pérez-Pampín, E.; Aldasoro, V.; Álvarez-Rivas, N.; et al.
Abstract : Background: Giant cell arteritis (GCA) is a large vessel vasculitis with a predisposition for the cranial branches of the external carotid artery. However, aorta and/or its main branches may also be involved ( 1–3 . Objectives: To assess the vascular territories most frequently affected in a series of patients with GCA who presented extracranial vessel involvement. Methods: Retrospective study of patients with GCA who presented compromise of extracranial vessels confirmed by PET/CT. Visual analysis of vascular uptake was performed on supra-aortic trunks (SAT), aortic arch (AA), thoracic aorta (TA), abdominal aorta (AA), iliac arteries (IA), lower limb arteries (LLA), and upper limb arteries (ULA). We carried out a comparative study between both sexes to see if there was any difference in the pattern of affectation. Results: We evaluated 68 patients with GCA (51W/17M) with a mean age of 68.06±8.33 years. The vascular territories affected were: TA (n=58, 85.29%), SAT (n=38, 55.88%), AA (n=28, 41.18%), AA (n=18, 26.47%), LLA (n=17, 25%), IA (n=13, 19.12%) and ULA (n=6, 8.82%). We also made a study of the number of vascular territories affected: 1 vascular territory (n=13, 19.12%), 2 territories (n=22, 32.35%), 3 territories (n=18, 26.47%), 4 territories (n=12, 17.65%) and more than 4 territories (n=3, 4.41%). Likewise, a comparative study between both sexes was conducted, in which only statistical significance was achieved in the involvement of ULA, which was more frequent in men (table 1). Conclusions: In patients with GCA the involvement of TA is very frequent, followed by the SAT and the AA. To a lesser extent, the AA and the LLA vessels are affected. The involvement of the IA and the ULA vessels is less frequent; the latter more frequently in men. On the other hand, the involvement of 2–3 vascular territories are the most frequent patterns. References: [1] Loricera J, Blanco R, Hernández JL, et al. Use of positron emission tomography (PET) for the diagnosis of large-vessel vasculitis. Rev Esp Med Nucl Imagen Mol. 2015;34:372–377. [2] Loricera J, Blanco R, Hernández JL, et al. Non-infectious aortitis: a report of 32 cases from a single tertiary centre in a 4-year period and literature review. Clin Exp Rheumatol. 2015;33:S19–31. [3] Loricera J, Blanco R, Hernández JL, et al. Tocilizumab in giant cella arteritis: Multicenter open-label study of 22 patients. Semin Arthritis Rheum. 2015;44:717–723. Disclosure of Interest: None declared